2018
DOI: 10.1016/j.powtec.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of moisture content in a fluidized bed dryer using an electrostatic sensor array

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Experimental investigations were conducted in a lab-scale FBD, the detail of which was given in reference [26]. Electrostatic sensor arrays were installed on the wall of the FBD to collect the electrostatic signals in the bed and a temperature and humidity sensor (Model HMP110, Vaisala) was installed at the outlet of the bed to obtain the temperature and humidity of the exhaust air.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental investigations were conducted in a lab-scale FBD, the detail of which was given in reference [26]. Electrostatic sensor arrays were installed on the wall of the FBD to collect the electrostatic signals in the bed and a temperature and humidity sensor (Model HMP110, Vaisala) was installed at the outlet of the bed to obtain the temperature and humidity of the exhaust air.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the features of the electrostatic signals in the time and frequency domains are applied to extract more information from the signals, which are applied to predict the variations of the moisture content in the FBD. However, due to the complex flow dynamics in the FBD, the electrostatic characteristics of the solid particles are influenced not only by the moisture content but also by the solids velocity [26]. As a result, the correlation velocity from the sensor arrays, which represents the solids flow behavior in the FBD, is also selected to be the input of the soft computing model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Wang et al [20] improved the measurement accuracy by applying the wavelet transform to the multiphase flow parameters. Considering that the signal measured by the ring electrode is an average feature over the entire cross-section, Zhang, Yang, and Dong's research found that the arc-shaped sensing electrode had an advantage in particle velocity and concentration distribution measurement in the monitoring of particle motion in gas-solid fluidized beds [21][22][23]. Qian also combined arc-shaped electrodes with digital images for the measurement of biomass-coal particles in fuel-injection pipelines [24].…”
Section: Introductionmentioning
confidence: 99%